Factors affecting the follow-up time after a positive result in the fecal occult blood test. - Yin-Wen Cheng (Public Library of Science (PLoS), 2021)
In 2010, Taiwan included the fecal occult blood test (FOBT) under preventive health insurance services. For patients whose test positive, receiving follow-ups is paramount. This study investigated factors affecting the follow-up time of these patients. This retrospective study used data from the colorectal cancer screening archives. The study period was from 2010 to 2013, and the subjects were 50-75-year-old persons who tested positive for FOBT. The t test, one-way ANOVA, and multiple regression were performed to address the differences in the mean tracking period between variables such as the population's demographic characteristics. The mean follow-up time for the 98,482 participants whose screening results were positive exhibited significant differences (p < 0.001) according to medical unit region and classification, age, screening location, family history, examination method, and diagnosis. The model predicting the mean follow-up time predicted a period of 10.079 days longer for those whose hospital was on an offshore island than that of those whose hospital was in the eastern regions. The follow-up time was 1.257 days shorter for people who were inpatients than those who were outpatients and was 8.902 days longer for people who underwent double contrast barium enema plus flexible sigmoidoscopy than those who underwent other examination methods. Patients with a family history of colorectal cancer and those whose examination results indicated cancer had a follow-up time of 2.562 and 2.476 days shorter than those who did not know their family history and those with other results, respectively. Factors affecting the follow-up time of people whose FOBT results were positive consisted of the location and classification of the follow-up institution, age, screening location, family history, examination method, and diagnosis. This provides valuable references for improving the cancer screening program.